KAJIAN PENGELOLAAN EKOSISTEM MANGROVE DI KELURAHAN KARIANGAU KECAMATAN BALIKPAPAN BARAT MELALUI PENDEKATAN EKONOMI - Nurul Ovia Oktawati; Erwan Sulistianto (Jurnal Harpodon Borneo, 2015)
The aims of the research are; 1) to identify both the potential and the types of utilization of mangrove ecosystem carried out by the local society; 2) to analyze the economic value of the mangrove ecosystem. The results show that the biggest utility is the one of crab that reaches Rp15,685,309,355 with the surplus consumer of Rp16,304,371,871,00. The biggest proportion is from the direct utilization with a percentage of 82.9% with a value of Rp57.610.284.092,00/year. Furthermore, the Total Economic Value of the mangrove forest ecosystem in Kariangau Village covering 2.037 ha amounts to Rp69.455.023.710,00.  Keywords : management, mangrove, Kariangau, West Balikpapan, economic